Suda çözünen metilenbisakrilamid piperazin kopolimerinin metal varlığında protein ile etkileşiminin incelenmesi - Aslan, Hayal (Fen Bilimleri Enstitüsü, 1997)
Bu çalışmada, N,N'-metüenbisakrilamid ile piperazinin oluşturduğu kopolimere üçüncü farklı alkilaminler eklenip, elde edilen polimerlerin çeşitli özellikleri incelenmiştir. Kopolimerdeki MBA miktarı sabit bırakılıp; %50, piperazin miktarı azaltılmış (%40), yerine seril amin ve oktilamin (%10) katılarak değişimler araştırılmıştır. Alkilamin katılarak elde edilen kopolimerlerin suda çözünürlükleri incelendiğinde, oktilaminle oluşturulan kopolimerin suda çözündüğü, setil aminin hidrofob yapısı dolayısıyla kopolimerin suda çözünmediği görüldü. Ayrıca suda çözünen oktilamin kopolimerinin çeşitli konsantrasyonlardaki NaOH ile hidroliz şartlan tespit edildi. Elde edilen polimerlerin özellikleri viskozimetrik İR ve UV ölçümleriyle belirlendi. Bu polimerlerin Cu2+ ve Fe2+ ile oluşturdukları kompleksler, absorbans ve pH ölçümleriyle incelendi.

Polymer that are dissolved in water have been studied in theorical polymer chemistry and in practical application areas. This so important for the polymers, which have been used as physicological active substances in immunologi. Therefore, study in this area have been continuing to have more information about the polymeric structures by using phyico-chemical methods. The synthetic polymers that contain nitrogen atoms in its structure have been used in medicine and biological sciences. As an example, effects of synthetic polymer are; the adjuvant effect (Secondary Chemical substances that enter to the organism to increase the immunity of organism with antigens), dissolving of sediments that prevent circulation of blood, antimicrobial effect, drug delivery system etc. There must be two different structures of polymers in order to using them in the medium of organism 1) Polymer must be resistant to enzymatic degradation to stay for a long time in the organism. For this reason, polymers must be combined with C-C sigma bonds 2) Polymers must have easily biodegredable bonds (C-N, C-S, C-O, C-P) to stay in an organism for a short time. The main aim in this study is to synthesize polymers that are biodegredable in the organism. On the other hand the new kind of physicological active polymers that contain C-N bonds in its structure will be synthesized and physico-chemical properties will be investigated. The importance of the copolymer with two components MBA-PP as a biologically active synthetic one is increasing rapidly, because of having C-N bonds and being of biodegredable in the medium of organism. However, there is no functional groups in the structure of the species so the molecule itself cannot give reactions with the proteins. It seems unreactive toward the proteins. VI To solve this problem, Copolymers with three components that consist of MBA, PP and primary alkyl amines (number of C>8, more hydrophobic character) are synthesized and their structures are investigated in IR, UV and viscozimetric measurements. And also the copolymers with two components (MBA-PP) may form complexes with several transition metal ions which have a mediator role between copolymer and protein to solve the reactivity problem. Piperazine-methylenebisacrylamide copolymer was obtained by using equal mole of each monomer. 2.1325 g N,N'-methylenebisacrylamide and 1.19 g piperazine were mixed with 7 m water. Polymerization was carried out under nitrogen and air atmosphere at 50°C. Properties at this copolymer have been investigated by using viscozimetric and IR measurement. The resulting polymer is water soluble. Polymerization occurs by migration of active H atoms of piperazine to the double bond of methylenebisacrylamide. The bond is broken down and monomers are bound to each other. CH2 = CH - CO -NH - CH2 -NH - CO - CH=CH2 + HN^ jm -> ffi^ ^N - CH2 - CH2 - CO -NH - CH2 -NH - CO - CH=CH2 + Hn( %JH + CH2 = CH -CO-NH-CH2-NH-CO-CH = CH2 -> T.. N^3^ ~ CH2CH2CONHCH2NHCO(CH2)2- N^N - CH2CH2CONHCH2NHCO(CH2)2-N..1 Addition of amine groups to above system that contain active hydrogen atom causes reaction between amine hydrogen with double bond of methylene bisacrylamide at the same time with piperazine. Thus, piperazine and other amine reacts with methylenebisacrylamide by means of competative reaction. On the basis of this knowledge, two kinds of primary alkyl amines (octyl and cetyl) are introduced to the mixture of methylenebisacrylamide and piperazine. Selection of these amines is based on their higher number of atoms. So the amines that contain different C atoms have different hydrophobic effect. The monomer ratio of MBA/PP is 1/1 at this polymerization reactino. When octylamine and cetylamine were introduced into polymerization, mole ratio of MBA is kept constant at 50%, piperazine is at 40% and alkylamine is 10%. Polymerization that occur by adding octylamine and cetylamin was done at the same conditions. Polymerization reaction could be represented schematically as follows. Vll t «m x O t-j X z CM x »_) 2 O UJ CM """"* CM ' 3= - 2 LJ V-J CM ""cm en I CM X +
The investigation of interaction of water soluble mba+pp copolymer with proteins in the presence of the metals
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1997
Keywords: Alkil aminler; Kopolimerler; Metilen bisakrilamid; Piperazin; Proteinler; Alkyl amines; Copolymers; Metilen bisakrilamid; Piperazine; Proteins